Media warfare content analysis of the conservative and alternative media during the Bukit Selambau Malaysian by-election. - Sajahan, Mohamed Samsudeen; Ahmad Zawawi, Azlyn; Andin Salamat, Azni Syafena; Kamarunzaman, Nur Zafifa; Mohd Yusof, Azrul Shahimy; Hussin, Zaliha; Jusoff, Kamaruzaman (Academic Journals, 2010)
This paper discuss on the role of the media in the context of warfare that was brought by the conservative mass media as well as the alternatives during the N 25 DUN Bukit Selambau, Malaysia by election time frame. The main idea of this study is to analyze the role of conservative and alternative media during Malaysia’s 2009 by-election. It should be noted that the types of media that were selected in this paperwork were not biased upon any parties and this was determined on the rationale that these media were the main choice of the local population. Among the local media sources that were chosen for this analysis were Utusan Malaysia, Berita Harian, Nanban, Tamil Nesan, whereas malaysiakini.com and tvantara.com were for the alternatives,. The discussions in this paperwork were more focused on the issues that were discussed by the media in terms of their main topic, news focus, themes, role of pictures and videos and the delivery of news. In order to deliver a more effective writing piece, the researcher had used two main communicative theories which were the theory of agenda setting as well as the framing theory in analyzing the impacts of media in this by-election.